2020
DOI: 10.1016/j.metabol.2020.154301
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor: Unexpected high mortality in COVID-19 and diabetic ketoacidosis

Abstract: Letter to the editor: Unexpected high mortality in COVID-19 and diabetic ketoacidosis To the EditorPatients with diabetes mellitus (DM) appear to be at a greater risk for severe symptoms and complications, including death from 2]. DM is a common comorbidity in patients affected with COVID-19 and may cause ketosis, ketoacidosis, and diabetic ketoacidosis (DKA) [3]. In patients with DM, acute hyperglycemic crises such as DKA and hyperosmolar hyperglycemic state can be precipitated by an acute illness such as COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 15 publications
6
66
1
Order By: Relevance
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 777 records were collected by the databases and manual searching. After the exclusion of the duplicates, review articles, case reports, pre‐printed versions without peer‐review, and irrelevant studies by title or abstract screening, 187 studies remained for full‐text review; 52 studies 6,17‐67 were finally included into the meta‐analysis, and 18 studies were included in the qualitative synthesis (Figure 1). A total of 52 records involving 10 614 COVID‐19 patients confirmed between December 25, 2019, and June 1, 2020, were included.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were performed in multicenters 6,17,23,34,45,49,57,58,60,64 . Among the included studies, 17 compared the ferritin level between groups with different severity of COVID‐19 18‐22,34,35,37‐39,44,50,53,56,61,64,65 and 18 compared its level between non‐survivors and survivors 6,17,23,24,26‐29,40‐42,45,46,52,55,58,63,66 . The characteristics of all studies included in this meta‐analysis are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The major issue that arises against the use of SGLT2 inhibitors in patients with COVID-19 is the potentially increased risk of diabetic ketoacidosis (DKA) in the context of an acute infection [7,8]. Protracted ketonemia, delay in DKA resolution, and high mortality among patients with COVID-19 and DKA pose significant concerns regarding the use of SGLT2 inhibitors in the acute setting, despite the fact that the rates of SGLT2 inhibitor usage in the aforementioned series were low [9,10].…”
Section: Dear Editormentioning
confidence: 99%
“…As with other severe infections [ 6 ], diabetic ketoacidosis (DKA) has been reported in patients with COVID-19 [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. With regard to coronaviruses, it has been shown that SARS-CoV (responsible for the SARS outbreak in 2003) binds to ACE2 in the pancreatic islets leading to islet damage and acute diabetes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical outcome of COVID-19 patients with DKA has been somewhat conflicting across studies; while one study found a mortality rate of 50% in COVID-19 patients with DKA [ 9 ], another study found that patients with DKA were more likely to survive compared to non-DKA patients [ 17 ]. Moreover, patients with combined DKA and HHS tend to have higher mortality than either DKA or HHS alone [ 29 ], however, similar comparative data in COVID-19 is lacking.…”
Section: Introductionmentioning
confidence: 99%